2019
DOI: 10.1590/s1984-29612019024
|View full text |Cite
|
Sign up to set email alerts
|

Crop residues activity against the free-living stages of small ruminant nematodes

Abstract: The nematicidal effect of different organic materials was evaluated in order to develop a non-chemical alternative soil treatment for control of the free-living stages of small ruminant gastrointestinal nematodes. The selected organic materials were residues from the juice industry of acerola, cashew, grape, guava, papaya and pineapple, as well as castor residue from the biodiesel industry. LC90 results showed that pineapple residue was the most efficient inhibitor of larval development, followed by castor, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…All the inputs were applied by hand before allowing the animals access to the pasture, considering the use of intensive grazing under continuous stocking, with a fixed stocking rate. The organic compost was considered a control because it has no anthelmintic effect in vitro, according to the methodology used by Salles et al (2019). The compost was based on the carcasses of small ruminants and was prepared as described by Meneses et al (2017).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the inputs were applied by hand before allowing the animals access to the pasture, considering the use of intensive grazing under continuous stocking, with a fixed stocking rate. The organic compost was considered a control because it has no anthelmintic effect in vitro, according to the methodology used by Salles et al (2019). The compost was based on the carcasses of small ruminants and was prepared as described by Meneses et al (2017).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…This strategy is based on the use of a fertilizer that reduces the contamination of grasses by infective larvae (L 3 ) and increases the amount of grass biomass, thereby contributing to reduce the L 3 .g -1 of dry mass, favor the nutritional levels of grass, and indirectly, the animal, by increasing the supply of food in the pasture. Salles et al (2019) evaluated several crop residues with anthelmintic effect in vitro and identified castor cake as a potential input to control the free-living stages of gastrointestinal nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore, widely employed in vegetable production, with good results and improved chemical and physical soil attributes (11) . In addition, because of its nematicidal effect, it controls gastrointestinal parasites in grazing sheep (6,7) , reducing the anthelmintic costs.…”
Section: Cienc Anim Bras V24 E-73410ementioning
confidence: 99%
“…The use of feed supplements, fertilizers, and anthelmintics allows maximizing animal production per area; however, it can burden the production system and, in some cases, compromise economic viability. In this scenario, the use of agroindustry by-products can contribute to the reduction of costs in livestock, either in the form of supplements, organic fertilizers, or the control of gastrointestinal parasites (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Facing this health concern, several studies have been developed to mitigate the negative effect caused by gastrointestinal nematodes, such as the use of breeds that are more resistant to worm infection, pasture management, use of energy diet, biological control, as well as the use of plants that have anthelminthic properties, and control strategies of the free-living stage of gastrointestinal nematodes in the soil (Vilela et al 2012 ; Miranda 2018 ; Salles et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%